不同Poincaré截面上齿轮扭振系统动力学特性分析 - 陈代林; 苟向锋 (Jixie chuandong)
Taking a typical single degree of freedom gear torsional vibration system as research object,study on non-smooth dynamics characteristic of the system is carried out.The contact surface and zero phase plane ψ0 are defined as Poincaré section,the bifurcation diagram,top Lyapunov spectrum and domains of attraction of the system on ψ0 section is calculated,the variation law of system Global and local response in the process of multiple attractors coexisting phenomenon produce and disappear is obtained.The bifurcat ion diagram of section is calculated,the periodicity of gear mesh-dismesh is obtained.T he waterfall spectrum diagram is calculated,the motion frequency response characteristic of gear mesh-dismesh is obtained.By comparing,it is found that gear system has abundant dynamics behavior on different Poincaré section.